2010
DOI: 10.1097/aap.0b013e3181e82e79
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Provides a Reliable Test of Local Anesthetic Spread

Abstract: This study shows that ultrasound is a reliable method of detecting injectate spread in a gelatin phantom model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…USG has gained popularity in regional anesthesia as it is safe, reliable, and precise 6 . The sensitivity of ultrasound to guide administration of local anesthetic (LA) is ranged from 85% to 92%, and the specificity around 90% to 95% 7 . In developing countries like Mexico, due to the unavailability of resource, we continue to rely on the blind surface landmark technique.…”
Section: Discussionmentioning
confidence: 99%
“…USG has gained popularity in regional anesthesia as it is safe, reliable, and precise 6 . The sensitivity of ultrasound to guide administration of local anesthetic (LA) is ranged from 85% to 92%, and the specificity around 90% to 95% 7 . In developing countries like Mexico, due to the unavailability of resource, we continue to rely on the blind surface landmark technique.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from BTX-A infiltration monitoring, the proposed method may be advantageous for other clinical applications, such as US guidance in regional anesthesia (Marhofer et al 2005;McCartney et al 2010;Andersen et al 2012;Sasaki et al 2017). Visual qualitative US guidance has been applied to monitor spread of local anesthetic, which allowed real-time identification of misdistributions of the anesthetic solution and guaranteed a faster onset time than the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that ultrasound is a reliable method of detecting injectate spread in a gelatin phantom model [8]. It has also been shown that ultrasound-guided circumferential injection of local anesthetic around the sciatic nerve can improve the rate of sensory block [9].…”
Section: Discussionmentioning
confidence: 99%